Design a PID controller based on grey wolf optimization algorithm for single-area load frequency control - Priyanka Jangid; Vishal Nagar; Aditya Sharma; Sonam Nagar; D. K. Palwalia (BIORE Scientia Academy, 2025)
This article, focuses on the load frequency control (LFC) of a single-area system with a grey wolf optimization metaheuristic approach. This approach is applied to optimize the PID controller parameters for the effective operation of the system. The grey wolf Algorithm (GWO) has been utilized to optimize the controller’s parameters and minimize the error. SIMULINK Model is used to simulate the Single-area load frequency control (SALFC) with GWO to mitigate the error and frequency fluctuations. The integral time absolute error (ITAE) has been considered as an objective function for optimal search of PID parameters. The frequency performance of the system has been observed without a controller, or any other methods in literature and with the proposed grey wolf optimization (GWO). The simulation response shows in terms of rise time, settling time, and peak time. The performance of the power system has been compared with other approaches namely Particle Swarm Optimization (PSO), and Firefly Algorithm (FFA). The Proposed optimization technique provides a much better response than other strategies.